Pengaruh Keterampilan Kerja, Motivasi, Lingkungan Kerja, dan Pelatihan Terhadap Produktivitas Karyawan di Industri Sarung Tenun Desa Parengan, Kabupaten Lamongan - Muhammad Aufal Marom; Moh. Azus Shony Azar; Saifuddin Zuhri (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study analyzes the effects of work skills, motivation, work environment, and training on employee productivity in the woven sarong industry of Parengan Village, Lamongan Regency. The study is relevant because micro and small-scale craft-based industries continue to rely heavily on skilled labor, manual production processes, and human resource management practices closely associated with family-run businesses. This research employed a quantitative explanatory approach involving 30 employees as respondents. Data were collected through a five-point Likert scale questionnaire based on indicators of work skills, motivation, work environment, training, and employee productivity. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results indicate that the research instruments were valid and reliable, and the regression model satisfied the assumptions of normality, showed no severe multicollinearity, and exhibited no symptoms of heteroscedasticity. Work skills, motivation, work environment, and training were found to have positive and significant effects on employee productivity, both partially and simultaneously. The work environment emerged as the most influential variable, followed by training, work skills, and motivation. The R-square value of 0.744 indicates that 74.4 percent of the variation in employee productivity can be explained by the four independent variables, while the remaining 25.6 percent is influenced by other factors outside the model. These findings highlight that the productivity of weaving workers should be enhanced through improvements in technical competencies, stronger employee motivation, better production environments, and training programs aligned with job requirements.